Evaluating The Quality of The Indonesia-English Translation of Research Abstracts Written By The Students Of Harapan Bangsa University - Dian Sukmawati, Ida; Hartono, Rudi; Sutopo, Djoko (Universitas Negeri Semarang, 2021)
This study was focused on evaluating the quality of the Indonesian-English translation of the research abstract written by the students of Harapan Bangsa University. The analysis included the analysis of translation quality in terms of accuracy, naturalness, acceptability, and readability as well as the translation ideology. The results of the study showed that the accuracy of the research abstract translation was dominated by highly accurate translation and less accurate translation in the target language which shared the same percentage as many as 36%. In terms of naturalness, it showed that 34% of the translation was categorized into highly natural. With regard to translation acceptability, it showed that 61% of the data belonged to acceptable. Meanwhile, in terms of translation readability, it showed that 75% of the data was categorized as readable. The register and genre of the research abstract texts and its translation were kept equivalent and holding the same purposes as it was translated overtly. In translating the research abstract text, it is suggested that the translator could highly consider the accuracy, naturalness, acceptability, and readability of the translation, particularly for target readers. With regard to the translation ideology, the translator is suggested to grasp the register and genre of the text before the translation process and regard the target readers to determine whether the text should be translated covertly or overtly.